Home Learning Environment and Screen Time Differentially Mediate the Relationship Between Socioeconomic Status and Preschoolers' Learning and Behavioural Profiles. - Bonifacci, Paola; Compiani, Diego; Vassura, Chiara; Affranti, Alexandra; Peri, Benedetta; Ravaldini, Viola; Tobia, Valentina (Child Psychiatry & Human Development, 2026)
Environmental variables related to the home context, including home literacy and numeracy, screen exposure and Socioeconomic Status (SES) are potential risks or protective factors for children's academic achievements and behaviour. The present multi-informant study aims to contribute to this issue by investigating SES's direct and indirect relationships in early learning (i.e., literacy, numeracy, and cognitive) and behavioural skills within a large sample of young children. One parent and one teacher for each of 1660 preschoolers filled out a questionnaire investigating SES, tablet and TV use, home learning activities, behavioural problems/strengths (parents' questionnaire), and children's learning skills and behaviour (teachers' questionnaire). Results of path analysis showed that tablet time and home learning environment mediate the effect of SES on early learning as assessed by teachers; as for the home learning environment, it was also a mediator of the relationship between SES and behavioural problems. Implications of these results for research in the field and educational policies are discussed.